The future of quantum in polariton systems: opinion - Liew, Timothy Chi Hin (2023)
A significant amount of control of exciton-polaritons has been achieved over the past decades, including their creation, localization in desired modes, coupling between modes, manipulation by control fields, and detection. As quantum particles maintain coherence (correlations) for some time and interact (causing the evolution of those correlations), exciton-polaritons underlie an emerging field of quantum polaritonics.